2020
DOI: 10.31491/apt.2020.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Aging pet cats develop neuropathology similar to human Alzheimer’s disease

Abstract: Aging pet cats can spontaneously develop Aβ deposition and tauopathy (including neurofibrillary tangle formation) with neuronal loss in a similar distribution and with similar characteristics to Alzheimer's disease (AD) in humans. These three major pathologies that characterize AD rarely occur spontaneously in other nonhuman animals. In addition, cats develop cognitive impairment with increasing age, and some studies show an association with neuronal lesions. These features suggest that the aging pet cat may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Domestic cats also develop plaques, tangles, and brain atrophy along with cognitive decline with age [ 184 , 236 , 237 ]. Research into age-related cognitive dysfunction in cats is not as well developed as that of dogs, but there is increasing interest in this area [ 185 , 238 , 239 , 240 ].…”
Section: Large Animal Models In Ad Researchmentioning
confidence: 99%
“…Domestic cats also develop plaques, tangles, and brain atrophy along with cognitive decline with age [ 184 , 236 , 237 ]. Research into age-related cognitive dysfunction in cats is not as well developed as that of dogs, but there is increasing interest in this area [ 185 , 238 , 239 , 240 ].…”
Section: Large Animal Models In Ad Researchmentioning
confidence: 99%
“…While dogs share many similarities with the human AD, cats are one of the only species which displays naturally occurring tau pathologies (Chambers et al 2015 ). It was shown that aging cats share three important similarities with human AD; they have spontaneous development of Aβ dispositions, and they have taupathies and neuronal loss which shares distribution and characteristics with AD (Klug et al 2020 ). Moreover, it has been shown that there is a correlation between the neuronal loss and cognitive dysfunction in aging cats (Takeuchi et al 2008 ).…”
Section: Animal Models For Alzheimer’s Disease: Laboratory Animals Vementioning
confidence: 99%
“…This makes the hunt for relevant biomarkers more difficult and unreliable. The most promising candidate for a model of AD is the domestic cat [7]. Amyloid plaques can be histologically detected in the brain of pet cats as early as 7 years of age [8,9].…”
mentioning
confidence: 99%